2014
DOI: 10.1186/ar4687
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms in rheumatology - a glucocorticoid perspective

Abstract: The hypothalamic-pituitary-adrenal (HPA) axis plays an important role in regulating and controlling immune responses. Dysfunction of the HPA axis has been implicated in the pathogenesis of rheumatoid arthritis (RA) and other rheumatic diseases. The impact of glucocorticoid (GC) therapy on HPA axis function also remains a matter of concern, particularly for longer treatment duration. Knowledge of circadian rhythms and the influence of GC in rheumatology is important: on the one hand we aim for optimal treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 48 publications
1
49
0
Order By: Relevance
“…Consequently, the diurnal profile of cortisol helps entrain peripheral tissue clocks. The HPA axis can also be activated by circulating cytokines such as IL-1, IL-6 or TNF, leading to a physiological negative feedback loop created by the immunomodulatory and anti-inflammatory properties of cortisol 34,35 . Importantly, cortisol and cytokines both have strong circadian profiles, supporting an integral crosstalk between the circadian timing system and the HPA axis.…”
Section: Key Pointsmentioning
confidence: 99%
“…Consequently, the diurnal profile of cortisol helps entrain peripheral tissue clocks. The HPA axis can also be activated by circulating cytokines such as IL-1, IL-6 or TNF, leading to a physiological negative feedback loop created by the immunomodulatory and anti-inflammatory properties of cortisol 34,35 . Importantly, cortisol and cytokines both have strong circadian profiles, supporting an integral crosstalk between the circadian timing system and the HPA axis.…”
Section: Key Pointsmentioning
confidence: 99%
“…Modern trials have confirmed that the efficacy of GCs can be significantly improved by administration as chronotherapy 28. In particular, low-dose MR prednisone effective at 02.00 am inhibits the proinflammatory sequelae of nocturnal inflammation better than GC administration in the morning, alleviating signs and symptoms related to pathways of circadian cytokines without increasing the risk of hypothalamus–pituitary–adrenal axis insufficiency in rheumatoid arthritis 29…”
Section: Discussionmentioning
confidence: 99%
“…Low salivary and urinary cortisol immediately following trauma have been reported to be predictors of PTSD suggesting that low cortisol concentrations may in fact be a preexisting vulnerability for developing PTSD rather than a consequence of PTSD [11]. Interestingly, inadequate cortisol secretion in relation to the chronic inflammation observed in rheumatoid arthritis, suggests that the suboptimal production of cortisol may be involved in onset and/or progression of autoimmune disease [12,13]. Hence, overlap may exist between the mechanisms by which low cortisol concentrations may precipitate both psychiatric and somatic diseases and disorders.…”
Section: Candidate Mechanisms Linking Ptsd and Immune Dysfunctionmentioning
confidence: 99%